2011
DOI: 10.1039/c1ob05971h
|View full text |Cite
|
Sign up to set email alerts
|

Chiral N-tert-butanesulfinyl α,β-unsaturated ketimine: a simple and highly effective olefin/sulfinimide hybrid ligand for asymmetric 1,4-additions

Abstract: One novel type of chiral olefin/sulfinimide hybrid ligands has been developed through a simple one-step condensation of α,β-unsaturated ketones with tert-butanesulfinamide and utilized successfully for rhodium-catalyzed asymmetric conjugated additions to furnish the desired adducts in high yields with excellent ee's.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…An easily accessible analogue of 94 (ligand 95), which was first synthesised by Ellman et al, 188 was also applied in the 1,4addition reaction (Table 3, Entry 22). 189 65 Fig. 66 Sulfinamide-alkene hybrid ligands Ligand 94 was employed by the group in two additional catalytic applications.…”
Section: Rhodium Catalysed 14-addition Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An easily accessible analogue of 94 (ligand 95), which was first synthesised by Ellman et al, 188 was also applied in the 1,4addition reaction (Table 3, Entry 22). 189 65 Fig. 66 Sulfinamide-alkene hybrid ligands Ligand 94 was employed by the group in two additional catalytic applications.…”
Section: Rhodium Catalysed 14-addition Reactionsmentioning
confidence: 99%
“…An easily accessible analogue of 94 (ligand 95), which was first synthesised by Ellman et al, 188 was also applied in the 1,4-addition reaction (Table 3, entry 22). 189 Ligand 94 was employed by the group in two additional catalytic applications. Firstly, for the kinetic resolution of Morita-Baylis-Hillman adducts by 1,4-addition/b-hydroxy elimination.…”
Section: Rhodium Catalysed 14-addition Reactionsmentioning
confidence: 99%
“…These chiral S/olefin ligands were successfully applied in Rh-catalyzed asymmetric 1,2or 1,4-additions, and formal [3+2] cycloadditions, giving the desired products with high levels of reactivity and enantioselectivity (Figure 2). [13]…”
Section: Chiral Olefin Hybrid Ligandsmentioning
confidence: 99%
“…Metal-catalyzed conjugated addition reactions of carbon nucleophiles to α,β-unsaturated compounds are the most widely used reactions for asymmetric carbon-carbon bond formation [ 1 , 2 , 3 ]. Much interest has recently been shown in rhodium-catalyzed conjugate addition of arylboronic acids to α,β-unsaturated carbonyl compounds [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ] using various ligands [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] such as biaryl bisphosphines [ 4 , 5 , 6 , 7 , 8 ], phosphoramidites [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ], diphosphonite [ 29 ], amidomonophosphines [ 30 , 31 ], N -heterocyclic carbenes [ 32 , 33 ], P-chiral phosphine [ 34 ], and dienes [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ,…”
Section: Introductionmentioning
confidence: 99%
“…Although many chiral ligands give adducts with good selectivity for cyclic enones, there are few ligands that give good results for both acyclic and cyclic enones. In addition, though conjugate addition of ortho -substituted arylboronic acids to α,β-unsaturated cyclic enones has been achieved in high enantioselectivities [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 21 , 44 ], there have been few reports on this reaction for acyclic enones [ 38 , 51 , 52 ]. On the other hand, we have already reported that a new bidentate phosphoramidite ligand (Me-BIPAM) based on O -linked-BINOL was synthesized and that a rhodium/Me-BIPAM complex was a better catalyst than several monodentate phosphoramidites for conjugate addition of arylboronic acids to α,β-unsaturated cyclic and acyclic carbonyl compounds [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%